BEAUTY STANDARDS AS SYMBOLIC VIOLENCE AGAINST WOMEN IN IMPERFECT: KARIER, CINTA, & TIMBANGAN (2019) - Muljadi, Hianly; Angjaya, Sonny; Deborah, Joanna (Paradigma: Jurnal Kajian Budaya, 2024)
Beauty is often perceived as a neutral concept; however, perceptions of beauty vary across different societies. In Indonesia, for instance, beauty is frequently associated with having fair skin and a slim physique. Consequently, women who do not meet these criteria are often deemed unattractive. Furthermore, beauty is commonly linked to a woman's success. This issue is critically examined in the 2019 film in Ernest Prakasa, Imperfect: Karier, Cinta & Timbangan, which centers on the life of a young woman named Rara, who is depicted as dark-skinned and slightly overweight. The societal pressures she faces to conform to prevailing beauty standards in pursuit of her dreams highlight the problematic nature of these standards. Additionally, the film portrays how even characters like Lulu and Debby, who fit the conventional beauty mold, are not immune to criticism. This study aims to explore the problematic nature of beauty standards and their impact on women, employing Pierre Bourdieu’s theory of capital and symbolic violence. The research concludes that beauty standards create unfair situations for women, perpetuating unattainable ideals that disproportionately affect them.